Implementasi Metode SMART (Simple Multi Attribute Rating Technique) Dengan Menggunakan Sistem Pendukung Keputusan Dalam Menentukan Karyawan Terbaik - Aida Shafira Chaidir Baadilla; Jaka Sutrisna (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Human resources are one of the important factors in the running of an agency. Good employee management will greatly affect the aspects of the success of the performance of the employees, if the employees can be well organized, it is expected that the company can run everything well. The problem of subjectivity in evaluating the performance of the best employees is almost unavoidable. To improve employee performance, companies really need to carry out the process of selecting the best employees in determining the best employees for each predetermined period. It is necessary to develop a computerized decision support system so that decision making in determining the best employees can be done quickly, precisely and accurately and free from subjectivity, by using a support system using the SMART method (Simple Multi Attribute Rating Technique).